Website Development for Karang Taruna as an Information Media: Pembuatan Website untuk Karang Taruna Sebagai Media Informasi - Syuhada, Fahmi; Adipta, Mara Zaenal; Anggarista, Randa (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2025)
This digital era presents both challenges and opportunities for youth organization such as Karang Taruna to enhace the effectiveness of communication and information dissemination through technology. This article documents a community service program aimed at assisting Karang Taruna by providing technology-based solution through the creation and training of website management. Using a participatory approach, this activity involved Karang Taruna members in all stages, including planning, design, development, and operational training. The reusult is a responsive website featuring key functionalities such as news, event agendas, photo galleries, and local tourism promotion. The website has proven to improve information delivery efficiency, expand community outreach, and support digital literacy among members. This program demonstrates that leveraging digital technology can serve as a catalyst for transforming community organizations toward more transparent, accounttable, and modern governance.